2009
DOI: 10.22605/rrh1154
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced in implementation of a telehealth enabled chronic wound care system

Abstract: Challenges faced in implementation of a telehealth enabled chronic wound care system Rural and Remote Health 9: 1154. (Online), 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Overall, the searches revealed several studies on cross‐sector TM interventions in chronic wound management, with the majority of them targeting wound healing, risk reductions, patient's quality of life, and cost‐effectiveness parameters. Only eight studies (see Table 2) explore broader or more comprehensive TM perspectives on quality improvement and integration of chronic wound management across sectors 27,33‐36,42,50,51 . Findings in three of these studies 42,50,51 are supported across databases and review methodologies applied in this article.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Overall, the searches revealed several studies on cross‐sector TM interventions in chronic wound management, with the majority of them targeting wound healing, risk reductions, patient's quality of life, and cost‐effectiveness parameters. Only eight studies (see Table 2) explore broader or more comprehensive TM perspectives on quality improvement and integration of chronic wound management across sectors 27,33‐36,42,50,51 . Findings in three of these studies 42,50,51 are supported across databases and review methodologies applied in this article.…”
Section: Resultsmentioning
confidence: 89%
“…These searches revealed several cross-sector publications that address wound healing and reduction (in size), risk of amputation, the accuracy of pressure injury evaluation, quality-adjusted life-year resulting from TM interventions or applications, and cost-effectiveness perspectives. 13,[37][38][39][40][41] We found broader or more comprehensive TM perspectives on quality improvement and integration of chronic wound management across sectors-extending beyond wound healing, risk reduction, and cost-effectiveness-only in studies by Mills et al 42 and Barrett et al 27 These studies documented several TM-related systemic opportunities and barriers to holistic (inpatient and outpatient) service quality improvement. Barrett et al 27 identified barriers in terms of delays in installing the software and workforce shortages, where only about half of those who trained in using the software were still employed at the end of the study.…”
Section: Google Scholar Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…An eHealth solution can belong to one of these domains or contain elements from several domains. 3 Research on eHealth has focussed on changed roles for healthcare professionals, [4][5][6] the importance of alignment with care processes, [7][8][9] impact of staff turnover, 10 increased workload 11 and/or decreased workload, [12][13][14] changes in workflow [15][16][17][18] and changes in professional values. 5,7,19 Consequently, previous research shows that eHealth solutions influence the way healthcare professionals conduct their work and provide care.…”
Section: Introductionmentioning
confidence: 99%
“…al note: "Several prior studies in community health research involving rural areas have found that positive community health results from professional-layperson partnerships engaged in capacity building, diverse leadership development and comprehensive multi-sectoral planning (150)." Further, Barret notes: "Clinical drivers and telemedicine users must own their own systems (151)." Hybrid leadership, as seen through Lara's encouragement of her staff and the multiple roles rural individuals fill within the community, is important for creating accountability within an implementation and community ownership, enabling successful implementations.…”
Section: Collaborative Efforts Can Only Truly Thrive If the People Or...mentioning
confidence: 99%